Las prácticas curativas atacameñas en Chile: entre el reconocimiento y la criminalización - Paola Bolados García (Nuevo mundo - Mundos Nuevos, 2011)
This paper explores the paradox of multicultural neoliberalism in Chile during the last two decades in the indigenous health field. On one hand, indigenous healing practices are recognized and promoted in the public health system (in this case Atacameñas indigenous healing practices). On the other hand, however, these practices are criminalized if they are seen to resist burocratization and neoliberalization in the space of intercultural health. As such, this paper covers the struggles and strategies for saliency and legitimacy on the part Atacameno indigenous health organizations and state-level mechanisms of control and regulation through the field of intercultural health.